Cyber-victimization and perceived depression: Serial mediation of self-esteem and learned-helplessness - Kususanto Ditto Prihadi; Yen Ling Hui; Melissa Jane Chua; Calvin K.W. Chang (Institute of Advanced Engineering and Science, 2019)
Literature suggests that the perception of being cyber-victimized is a stronger predictor of depression symptoms than the perception of being victimized offline, and that learned-helplessness can explain the prediction of perceived cyber-victimization on perceived depression. Nevertheless, other studies suggested that the link between perceived cyber-victimized and learned-helplessness is weakened by state self-esteem. This study investigates the double mediation effect of state self-esteem and learned-helplessness on the relationship between perceived cyber-victimized and perceived depression. 104 participants between 18 and 30 years of age (63 females, 41 males, 1 prefer not to say) have been recruited through haphazard sampling method to fill in the Cyberbullying Victimization Scale, State Self-Esteem Scale, Learned Helplessness Scale, and Beck’s Depression Inventory. Our findings suggest that the double mediation effect occurs. As a conclusion, our findings suggested that cyberbullied social media users will only fall into perceived depression when their state self-esteem is also negatively affected by their perception of being cyberbullied, up to the point where they learn that they are helpless. Further implication are discussed at the end of the paper.